Rural development for small farmers in the Andean region through diversification of production activities for new markets - Instituto Interamericano de Cooperación para la Agricultura (IICA) (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2020)
The objetive of this proposal is to begin identifying the real alternatives that exist for incorporating a large portion of small farmers into production processes aimed at special market niches for nontraditional agricultural products. The specific objective is to draw up guidelines for a proposal to involve small farmer organizations in the Andean region in the production and marketing of non-traditional agricultural products such as tropical fruit, vegetables, plants, roots, tubers and spices, in accordance with market opportunities and comparative advantages. The paper then refers to activities to be undertaken during the preparation of guidelines for the proposal; to the strategy that should be both short and medium term in scope; and the institutions involved in executing the short term actions of phase one. The costs involved in the short term phase of the proyect appear at the end.